The Role Of Independence And Effectiveness Of Internal Audit To Good University Governance - Dwi Sulistiani; Fantika Febry Puspitasari; Siti Ma'rifatul Hasanah (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study aims at providing an empirical evidence of the effectiveness of the Internal Audit (IA) as a mediating variable in the association of IA independence and Good University Governance (GUG). Methodology/approach: A quantitative research using survey methods was carried out by applying Wrap PLS software for the data processing. The primary data were in the form of questionnaires, which were distributed to IA unit members from 58 state Islamic higher education institutions in Indonesia. There are 107 questionnaires that are accepted and processed. Findings: The results show that independence does not influence GUG directly. However, the effectiveness of IA proved the capability of mediating the relationship between IA independence and GUG. Internal auditors in higher education institutions are still unable to fully maintain their independence. It happened because, apart from being an auditor, lecturers act as auditees in their capacity as educators. Practical implications: For policymakers, the results of this research can be used as an input or a basis for establishing new regulations, especially regarding IA in Higher Education. For State Islamic Higher Education, this study provides recommendations for the need to increase the independence and effectiveness of the IA because it can support the achievement of GUG. Originality/value: This study uses IA objects in state Islamic universities throughout Indonesia. This research model is different from previous research by placing IA effectiveness in the relationship between IA independence and GUG.